2018
DOI: 10.2147/dddt.s159965
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a combined wet milling process in order to produce poly(vinyl alcohol) stabilized nanosuspension

Abstract: PurposeThe article reports a wet milling process, where the planetary ball mill was combined with pearl milling technology to reach nanosize range of meloxicam (Mel; 100–500 nm). The main purpose was to increase the dissolution rate and extent of a poorly water-soluble Mel as nonsteroidal anti-inflammatory drug as well as to study its permeability across cultured intestinal epithelial cell layers.MethodsViscosity of milled dispersion and particle size distribution and zeta potential of Mel were investigated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…It should be noted that recently the characterization of the investigated materials (e.g., crystallinity) using DSC as a semiquantitative conventional method has become common in scientific research [7][8][9]. It provides a possibility to predict the crystallinity of the examined materials, but to verify the accuracy of thermoanalytical measurements, the X-ray powder diffraction test is required [10,11]. In our work, it was found that the degree of crystallinity of Mel investigated by DSC and XRPD did not show any significant difference at 95% significance level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that recently the characterization of the investigated materials (e.g., crystallinity) using DSC as a semiquantitative conventional method has become common in scientific research [7][8][9]. It provides a possibility to predict the crystallinity of the examined materials, but to verify the accuracy of thermoanalytical measurements, the X-ray powder diffraction test is required [10,11]. In our work, it was found that the degree of crystallinity of Mel investigated by DSC and XRPD did not show any significant difference at 95% significance level.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, the Mel amount was 10% (w/w) and 5% (w/ w) of PVA proved to be an optimal quantity to meet the expected particle size range. During the milling, a high level of amorphization was detected with DSC and XRPD examinations [10]. In this milling system, the ratio of the started pre-suspension and pearls 1:1 (w/w) resulted in about 200-fold particle size reduction in one step.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Ball Mill tersebut terbuat dari logam (36) yang disyaratkan mempunyai karakteristik keras (37) sekaligus tangguh (tidak mudah pecah) dan tahan korosi (38) untuk menanggung beban dan lingkungan selama proses penggilingan materi. Banyak faktor-faktor yang berpengaruh terhadap hasil dari proses milling ini seperti kecepatan (39) , waktu, temperatur (40) , tekanan, ukuran grinding ball, persentasi PCA (Process Control Agent), dan komposisi berat serbuk tersebut.…”
Section: End Millingunclassified